In Silico Characterization of Ageratum Enation Virus, Ageratum Leaf Curl Betasatellite and Marigold Leaf Curl Alphasatellite Infecting an Important Ornamental Plant Marigold (Tagetes Patula) in Indian Subcontinent. - Marwal, Avinash; Prajapat, Rajneesh; Gaur, R K (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Ornamental plants act as an alternate host of begomoviruses and its associated satellite molecules in the absence of main crop. Marigold (Tagetes patula) an important ornamental plant, widely cultivated in India were found infected with three begomovirus components i.e. Ageratum enation virus (AEV: KC589699), Ageratum leaf curl betasatellite (ALCB: KC589700) and Marigold leaf curl alphasatellite (MLCuA: KC206078). This study supported evidence that virus associated with Marigold was studied through In Silico analysis for in depth study. The phylogenetic studies revealed closeness to other virus prominent in other neighbouring countries and can be replicated by other begomovirus species which increases the possibility of recombination and reassortment events.